Editorial (Condensed Matter Physics, 2002)
This number consists of two parts. The first part (p. 211–306) is a
continuation of a collection of papers devoted to theoretical, numerical
and experimental studies in the field of star polymers¹. The second
part (p. 307–362) is a supplement to the special issue dedicated to
Jean-Pierre Badiali on the occassion of his 60th birthday².